Predictive Value of QT Interval for Postoperative Atrial Fibrillation in Patients Undergoing Off-Pump Coronary Artery Bypass Surgery - Kumtepe,Gencehan (2022)
ABSTRACT Introduction: Postoperative atrial fibrillation (poAF) is a common complication of coronary artery bypass grafting, and its reasons are still the subject of research. The aim of this study was to evaluate whether QT interval is related to new onset of poAF occurrence. Methods: This study included 167 patients undergoing elective isolated off-pump coronary artery bypass grafting (OPCAB) surgery. Patients were divided into two groups as poAF (+) and poAF (-), according to the development of poAF, and the results of the measurements were compared between the groups. Results: PoAF was detected in 37 (22.1%) of 167 patients who underwent OPCAB surgery. When QT interval measurements were compared, preoperative and postoperative QT and corrected QT interval (QTc) values were significantly longer in the group with atrial fibrillation. Mean values of preoperative QT were 407.5±27.1 in the poAF (-) group vs. 438.5±48.5 in the poAF (+) group (P<0.001). Mean values of preoperative QTc were 419.1±14.5 in the poAF (-) group vs. 448.5±26.6 in the poAF (+) group (P<0.001). Mean values of postoperative QT were 416.3±48.3 in the poAF (-) group vs. 439.2±45.8 in the poAF (+) group (P=0.005). And mean values of postoperative QTc were 419.8±12.5 in the poAF (-) group vs. 452.0±23.3 in the poAF (+) group (P<0.001). Conclusion: QT interval measurement may be a new parameter in predicting poAF development after OPCAB surgery.